Optimal nondiscriminatory auctions with favoritism - Arozamena, Leandro Roberto (2014)
In many auction settings, there is favoritism: the seller´s welfare depends positively on the utility of a subset of potential bidders. However, laws or regulations may not allow the seller to discriminate among bidders. We find the optimal nondiscriminatory auction in a private value, single-unit model under favoritism. At the optimal auction there is a reserve price, or an entry fee, which is decreasing in the proportion of preferred bidders and in the intensity of the preference. Otherwise, the highest-valuation bidder wins. We show that, at least under some conditions, imposing a no-discrimination constraint raises expected seller revenue.